EFNA3 Is a Prognostic Biomarker Correlated With Immune Cell Infiltration and Immune Checkpoints in Gastric Cancer - Zheng, Peng; Liu, XiaoLong; Li, Haiyuan; Gao, Lei; Yu, Yang; Wang, Na; Chen, Hao (Frontiers in Genetics, 2022)
Background: Ephrin A3 (EFNA3), like most genes in the Ephrin family, plays a central role in embryonic development. However, the relationship between EFNA3 and gastric cancer (GC) prognosis and tumor-infiltrating lymphocytes is unclear. Methods: Tumor Immune Estimation Resource (TIMER) site and Gene Expression Profiling Interactive Analysis 2 (GEPIA2) were used to analyze the expression of EFNA3, Kaplan-Meier plotter and GEPIA2 were used to evaluate GC prognosis. Gene set enrichment analysis (GSEA) was performed using the TCGA dataset. TIMER database and CIBERSORT algorithm studied the relationship between EFNA3 expression and immune infiltration in GC. cBioPortal explores genomics and the relationship between EFNA3 and immune checkpoints. Finally, quantitative real-time polymerase chain reaction (qRT-PCR) was performed to detect EFNA3 expression in GC cells and tissues. Results: The expression of EFNA3 in GC tissue was higher than normal gastric. The higher expression of EFNA3, the worse overall survival (OS), disease-free survival (DFS) and First Progression (FP) in GC patients. GSEA identified MYC_TARGETS_V1, E2F_TARGETS, DNA_REPAIR, G2M_CHECKPOINT, MTORC1_SIGNALING and CHOLESTEROL_HOMEOSTASIS differentially enriched in high EFNA3 expression pathway. The infiltration of B Cells, CD8+T Cells, CD4+T Cells, Macrophages, neutrophils and Dendritic Cells were negatively correlated with immune markers. EFNA3 had collinearity with multiple immune checkpoints. Finally, it is conformed that the higher mRNA expression of EFNA3 in GC cell, and the higher expression of EFNA3 had worse prognosis in GC patients. Conclusion: EFNA3 can be used as a prognostic marker for the prognosis and immune infiltration of GC patients.